The sentence intelligibility in different types of noise regarding people with a normal hearing ability - Vokřál, Jan; Dlouhá, Olga (Prague Medical Report, 2009)
The capability of speech understanding can be tested in the form of sentences. This report describes the origin of a new test in the Czech language to evaluate the sentence intelligibility with the presence of the competitive disturb noise. The results of the test depend on the test project, sentence material, competitive signal, test evaluation, and hearing conditions. Pilot results were obtained from 3 different noises (Speech noise, Babble noise, Cocktail party noise) at 16 people with a normal hearing ability. The Speech noise, which is recommended by a technical standard, mask sentences very poorly. On the other hand, the Babble noise and the Cocktail party noise, which are used to mask sentences in different languages, mask at lower intensities.
Keywords: financování organizované; dospělí; hluk; Financing, Organized; Middle Aged; lidé středního věku; Noise; lidé; audiometrie; Speech Discrimination Tests; testy sluchového rozlišování; Audiometry; Adult; Humans